2016
DOI: 10.1016/j.annemergmed.2015.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Distal Ureteric Stones and Tamsulosin: A Double-Blind, Placebo-Controlled, Randomized, Multicenter Trial

Abstract: We found no benefit overall of 0.4 mg of tamsulosin daily for patients with distal ureteric calculi less than or equal to 10 mm in terms of spontaneous passage, time to stone passage, pain, or analgesia requirements. In the subgroup with large stones (5 to 10 mm), tamsulosin did increase passage and should be considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
113
1
6

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(124 citation statements)
references
References 27 publications
4
113
1
6
Order By: Relevance
“…Because tamsulosin was the most commonly used to promote ureteral stones expulsion, we made a comparison Silodosin with tamsulosin. [28][29][30] The results demonstrated that compared with tamsulosin, there was a 20% improvement of stone clearance in Silodosin group. For expulsion time, compared to control, other alpha-blockers could shorten 2.91 days and Silodosin could shorten 4.5 days.…”
Section: Discussionmentioning
confidence: 66%
“…Because tamsulosin was the most commonly used to promote ureteral stones expulsion, we made a comparison Silodosin with tamsulosin. [28][29][30] The results demonstrated that compared with tamsulosin, there was a 20% improvement of stone clearance in Silodosin group. For expulsion time, compared to control, other alpha-blockers could shorten 2.91 days and Silodosin could shorten 4.5 days.…”
Section: Discussionmentioning
confidence: 66%
“…However, the data from several recent well-planned randomized clinical trials did not shown the MET benefits in patients with ureteric stones [19,20].…”
Section: Discussion Of Results Of the Studymentioning
confidence: 99%
“…6,9,15 Furthermore, a recently published trial suggested that patients with large stones (5 to 10 mm) benefited from tamsulosin, whereas those with smaller stones (<5mm) did not. 9 We hypothesized that stone size modified the effect of tamsulosin and accounted for between-study heterogeneity, or could help resolve discrepancies between "negativeresult" multicenter trials and previous meta-analyses. 16 Thus, we sought to conduct a prespecified analysis comparing the effect of tamsulosin in a small-stone (<5 mm) versus large-stone (5 to 10 mm) subgroup.…”
Section: Data Collection and Processing And Primary Data Analysismentioning
confidence: 99%
“…We also conducted a subgroup analysis (stone size <5 versus 5 to 10 mm) to determine whether stone size modifies the effect of tamsulosin, as suggested by the latest trial. 9 This study will clarify the role of tamsulosin in patients receiving a diagnosis of ureteral stones less than 10 mm that do not require urgent intervention.…”
Section: Goals Of This Investigationmentioning
confidence: 99%
See 1 more Smart Citation